A new method for the determination of the entry position of y-rays [gamma rays] in high purity germanium detectors by current pulse analysis - Palafox Gamir, Luis (Cranfield University, 1997)
A new method for determining the entry point of gamma-rays in closed ended HPGe detectors has been developed. Exploiting the position dependence shown by the current pulses generated when a gamma-ray interacts with the detector, it is possible to electronically divide the crystal in the radial coordinate and thus increase the effective granularity of the detector. Position resolution is particularly important for correcting the Doppler peak broadening observed in many in-beam gamma-spectroscopy experiments. Position resolution within coaxial crystals is accomplished by combining the angular information gained by segmenting the outer contact with the determination of the event radius by current pulse shape analysis. With increasing gamma-energy, more than one interaction is in general required to completely stop a gamma-ray in a germanium detector. The concept of a main interaction, defined as that depositing the largest fraction of the original gamma-energy, is introduced and seen to be the dominant contribution to the event current pulses. A Monte Carlo simulation for the positions and energies of the interactions in an event has been performed in order to establish the physical limits for the position resolution that can be measured in a segmented CLUSTER module. A varying fraction of events, from 55% at a gamma-energy of 400 keV to 85% at 1800 keV, have their main interaction within 5 mm from the entry point. The position of the main interaction can therefore be successfully used to measure the entry position of the gamma-ray in the detector. In order to provide high quality charge/energy and current outputs from the detector signal, a new preamplifier for large volume HPGe detectors has been developed. The intrinsic equivalent noise contribution from the preamplifier was measured at 0.65 keV + 35 eV /pF. The measured energy resolution when the input FET is operated at cryogenic temperature is 2.30 keV at 1333 keV with 3 μs shaping time. Using this preamplifier and the first prototype of a two-fold segmented CLUSTER module, a radial resolution of ±4mm has been measured with the new method both at 662 and 1333 keV. The method can be incorporated into an analogue electronic circuit and is therefore directly applicable in in-beam gamma- spectroscopy experiments.